2012
DOI: 10.2140/pjm.2012.256.67
|View full text |Cite
|
Sign up to set email alerts
|

Deformation retracts to the fat diagonal and applications to the existence of peak solutions of nonlinear elliptic equations

Abstract: We consider the equation −ε 2 u = u p − u q in a bounded, smooth domain ⊂ ‫ޒ‬ N with homogeneous Dirichlet boundary conditions when eitherWe prove the existence of multiple positive solutions in the case of small diffusion provided the domain is not contractible.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…In particular, Dancer and Yan ( [10]) proved that if the domain has a nontrivial topology, then there always exists a k-peak positive solution for any k ≥ 1. This result has been generalized by Dancer, Hillman and Pistoia ( [9]) to the case of a not contractible domain. On the other hand, Dancer and Yan ( [11]) showed that if Ω is a strictly convex domain and k ≥ 2, then problem (1.1) does not admit a k-peak positive solutions (see also [24] for the proof when k = 2).…”
Section: Introductionmentioning
confidence: 71%
“…In particular, Dancer and Yan ( [10]) proved that if the domain has a nontrivial topology, then there always exists a k-peak positive solution for any k ≥ 1. This result has been generalized by Dancer, Hillman and Pistoia ( [9]) to the case of a not contractible domain. On the other hand, Dancer and Yan ( [11]) showed that if Ω is a strictly convex domain and k ≥ 2, then problem (1.1) does not admit a k-peak positive solutions (see also [24] for the proof when k = 2).…”
Section: Introductionmentioning
confidence: 71%
“…By using the Lyapunov-Schmidt reduction, the authors proved the existence of positive multi-peak solutions under the homogeneous Dirichlet boundary condition in a general domain Ω with nontrivial topology. For the further related results, we refer to [6,14,19,21,23] and the reference therein.…”
Section: Introductionmentioning
confidence: 99%